MicroRNA-155 Protects Group 2 Innate Lymphoid Cells From Apoptosis to Promote Type-2 Immunity - Knolle, Martin D.; Chin, Shau Bing; Rana, Batika M. J.; Englezakis, Alexandros; Nakagawa, Rinako; Fallon, Padraic G.; Git, Anna; McKenzie, Andrew N. J. (Frontiers in Immunology, 2018)
Group-2 innate lymphoid cells (ILC2) play critical roles in the initiation and maintenance of type-2 immune responses, predominantly through their production of the type-2 cytokines IL-5, IL-9 and IL-13. ILC2 are essential for the efficient elimination of helminth parasites, but also contribute to the detrimental type-2 immune responses that underlie diseases such as asthma and allergy. While several transcription factors have been identified that regulate the development and function of ILC2, less is known about the post-transcriptional mechanisms that regulate these processes. We identified micro-RNAs (miRNAs) that are co-ordinately regulated in ILC2 from mice exposed to two different stimuli, namely IL-33 “alarmin” administration or Nippostrongylus brasiliensis parasitic worm infection. miR-155 is upregulated in ILC2 in response to both stimuli and miR-155-/- mice had impaired IL-33-driven ILC2 responses. Using mixed bone marrow chimeras, we demonstrate that this deficit is intrinsic to ILC2 and that miR-155 protects ILC2 from apoptosis, while having no impact on ILC2 proliferation or cytokine production. These data reveal a subset of miRNAs that are regulated upon ILC2 activation and establish a specific role for miR-155 in regulating ILC2 survival following activation.